As orientações pedagógicas da educação infantil em municípios de Santa Catarina - Wiggers, Verena (2007)
The study analyzes the pedagogical guidelines for early childhood education, adopted by municipalities of the state of Santa Catarina, Brazil. The research was done using a questionnaire, which was sent to all the cities in the state; it was also requested that they sent documents with their pedagogical guidelines for the municipal nurseries and preschools. The questionnaires collected general data on educational services for zero to six years old children. The questionnaire obtained answers from 73 cities, which means 25% of the total. Sixty cities affirmed that they had prepared pedagogical guidelines since January, 1st of 2001 and 36 of them declared that they produced a document. However, only 17 cities allowed them to be analyzed. In order to examine the documents content, some procedures were applied, using the Nud*ist informatics software. The questionnaire data allowed relating the characteristics of the documents to the educational context of the different municipalities, taking in account their diverse economic, social, cultural and political conditions. The thesis main conclusions points out the main deficiencies of most documents, considering the needs of the early childhood education institutions. The document prepared by the Ministry of Education - MEC, Referenciais Curriculares Nacionais para a Educação Infantil - RCNEI (1998)/ National Curricular Referential is the best well-known document, and probably, the one that is more adopted as a basis for the municipal documents. Another official document, Diretrizes Curriculares Nacionais para a Educação Infantil/ National Curricular Guidelines for Early Childhood Education, although mandatory, are less cited as subsidy for documents. In fact, the nature of documents was very diverse, up from general pedagogical guidelines, until bureaucratic rules. Some of them seemed to be prepared by schools individually. Perhaps, predominance of using RCNEI may explain the cognitive emphasis and the eclectic orientation of many documents. Other documents are based on another theoretical orientation, proposed by critics of the RCNEI, who plead for a pedagogical practice that minimizes the teacher s dominance and focalizes on the needs of children s development and on their different languages. This thesis tries to indicate limitations of both perspectives, highlighting the importance of a general education and the different possibilities of human culture as learnings contentsfor day care centers and preschools